Preparation of azidobrevianamide A and synthetic and biological studies of tetrazomine - Tippie, Tracy N., author; Williams, Robert M., advisor (Colorado State University. Libraries, 1995)
The regioisomers 5-azidobrevianamide A and 7-azidobrevianamide A were synthesized from natural (+)-brevianamide A. The synthesis involved nitration, reduction to the amine, formation of the diazonium ion, and reaction with azide ion. These compounds might be of potential use as photo-affinity labeling agents for the isolation of a potential enzyme catalyzing a Diels-Alder reaction in the proposed biosynthesis of brevianamide A and B. Synthetic studies were conducted towards the total synthesis of tetrazomine. A methodology was devised which allows regioselective introduction of nitrogen functionality to the aromatic ring of an isoquinolone system which is an intermediate in a synthetic pathway to the structurally related quinocarcin. The methodology involves the use of a chloride atom as a "blocking" group, followed by regioselective nitration, and simultaneous cleavage of the chloride and reduction of the nitro moiety furnishing the desired amine. The synthesis of the P-hydroxypipecolinic acid (1 R, 2 R)-1-carboxy-2-hydroxypiperidine was achieved via a stereoselective aldol condensation with a chiral glycine template and 4-pentenal. Following reductive ozonolysis the amino acid was generated by a novel one pot transformation in which a protecting group was cleaved, reductive amination realized and the chiral auxiliary of the template cleaved to furnish the substituted piperidine. It was found that under anaerobic conditions tetrazomine undergoes a redox self-disproportionation of the oxazolidine moiety in an analogous manner to quinocarcin. The oxidized and reduced products were isolated by HPLC and characterized. It was proposed that under aerobic conditions tetrazomine generates superoxide via the proposed disproportionation which could ultimately generate hydroxyl radical by Haber- Weiss/Fenton chemistry. Elucidation of this mechanism provided the first evidence of the relative stereochemical configuration of tetrazomine. It was also shown using a 32P-5'-end labeled synthetic oligionucleotide and high-resolution polyacrylamide gel electrophoresis that tetrazomine is capable of DNA nicking in a non-sequence-specific oxygen dependent fashion characteristic of Fenton-mediated DNA damage.
Keywords: Tetrazomine; Biosynthesis